Inclusion complexation of the anticancer drug pomalidomide with cyclodextrins: fast dissolution and improved solubility - Szabó Zoltán-István; Orbán György; Borbás Enikő; Csicsák Dóra; Kádár Szabina; Fiser Béla; Bela Fiser; Фішер Бейло; Dobó Máté; Horváth Péter; Kiss Eszter; Budai Lívia; et al. (Elsevier, 2021)
Abstract. Pomalidomide (POM), a potent anticancer thalidomide analogue was characterized in terms of cyclodextrin complexation to improve its aqueous solubility and maintain its anti-angiogenic activity. The most promising cyclodextrin derivatives were selected by phase-solubility studies. From the investigated nine cyclodextrins – differing in cavity size, nature of substituents, degree of substitution and charge – the highest solubility increase was observed with sulfobutylether-β-cyclodextrin (SBE-β-CD). The inclusion complexation between POM and SBE-β-CD was further characterized with a wide variety of state-of-the-art analytical techniques, such as nuclear magnetic resonance spectroscopy (NMR), infrared spectroscopy (IR), circular dichroism spectroscopy, fluorescence spectroscopy as well as X-ray powder diffraction method (XRD). Job plot titration by NMR and the AL-type phase-solubility diagram indicated 1:1 stoichiometry in a liquid state. Complementary analytical methods were employed for the determination of the stability constant of the complex; the advantages and disadvantages of the different approaches are also discussed. Inclusion complex formation was also assessed by molecular modelling study. Solid state complexation in a 1:1 M ratio was carried out by lyophilization and investigated by IR and XRD. The complex exhibited fast-dissolution with immediate release of POM, when compared to the pure drug at acidic and neutral pH. Kinetic analysis of POM release from lyophilized complex shows that Korsmeyer-Peppas and Weibull model described the best the dissolution kinetics. The cytotoxicity of the complex was tested against the LP-1 human myeloma cell line which revealed that supramolecular interactions did not significantly affect the anti-cancer activity of the drug. Overall, our results suggest that the inclusion complexation of POM with SBE-β-CD could be a promising approach for developing more effective POM formulations with increased solubility.
Editorial Board: https://www.cell.com/heliyon/editors
Contents: https://www.cell.com/heliyon/issue?pii=S2405-8440(20)X0008-9
Keywords: Pomalidomide; Cyclodextrin complexation; Inclusion complex; Solubility; Comparative dissolution; Pomalyst